An unusual presentation of cerebellar lymphoma. (November 2018) - Harley, Benjamin; Shivapathasundram, Ganeshwaran; Astradsson, Arnar; Muthurajah, Vanaja; Wickremesekera, Agadha
Highlights: EBV associated lymphoma is a recognised complication in immunosuppressed patients. Primary CNS lymphoma is rare, particularly involving the posterior fossa. A myasthenia gravis patient treated with azathioprine developed a rare lymphoma. Abstract: We report a case of a 40 year old female who presented with a three month history of headaches with a background of Myasthenia Gravis (MG), treated with azathioprine. MRI brain demonstrated a rim-enhancing lesion in the left posterior fossa. CT scan of the chest abdomen and pelvis revealed no other lesion. The patient was taken for resection of the lesion via left retrosigmoid approach. Histologically the neoplasm was a large B-cell lymphoma, Epstein-Barr virus (EBV) positive, with clonality confirmed by IGH gene rearrangement studies. To the best of our knowledge this is the first case of primary central nervous system (CNS) EBV-positive diffuse large B-cell lymphoma of the posterior fossa in a patient with MG treated with azathioprine.